UNIVERSITY EDUCATIONAL SERVICES MARKETING: FEATURES, OPPORTUNITIES, PROBLEMS - Amerkhanova A. B.; Meshkov V. R. (Scientific Journal of Pedagogy and Economics, 2019)
In the new socio-economic conditions for Kazakhstan, educational institutions are forced to be active market actors, independently formulating an offer, providing and selling their educational services. The interest of universities in the search for opportunities to increase the competitiveness of educational services is beyond doubt. In this work, the author defines some features of educational services as a subject of marketing activities of an educational institution, specifies the marketing potential in the field of higher professional education. The prospect of applying marketing innovations for the development of educational services has been identified.